Evaluation of usefulness of doppler angiography in differential diagnosis of malignant and benign breast lesions in women during menopause - Dębniak, Bogusław; Kramer, Lucyna; Dubiel, Mariusz (Menopause Review/Przegląd Menopauzalny, 2003)
Objective Newly formed capillars have chaotic, often sinusoid network with frequent arteriovenous fistulas leading to unproper blood flow. Evaluation of blood perfusion in breast tissue by the use of color doppler under such circumstances is difficult. The aim of our study was to evaluate the usefulness of doppler angiography (DA) with computer analysis of recorded signals in differential diagnosis of malignant and benign breast tumors in women during menopause. Materials and methods Recording of signals in the system of doppler angiography (DA) was performed in 24 patients with benign breast tumors and 38 patients with breast cancer. Control group consisted of 37 healthy women during menopause. The evaluation of the blood perfusion in benign and malignant breast tissues and healthy tissues was done with an Acuson 128XP (Acuson Corp., Mountain View, Kalifornia, USA) using 7 Mhz „real-time” transducer with a doppler angiography option. DA images were recorded on S-VHS videotape and transmitted for computer analysis to PC with a QuickCapture frame grabber board (Data Translation Inc., USA). The image was analysed with the HLImage++ 97 software, enabling evaluation of 8-bit pictures in 256 gray scale. The result was the semi-quantitative evaluation of blood perfusion within the organ. Results In examined group all values of DA signals, both in patients with malignant and benign breast tumors, were above upper limits of the reference line. Blood perfusion was larger in breast cancer in comparison to benign lesions (p<0.0001); it was also larger in benign lesions in comparison to healthy breast tissues (p<0.00001). Conclusion High sensitivity and specificity of doppler angiography in differential diagnosis of malignant and benign breast lesions allows to consider this method as an important tool of sonomammography.